2007
DOI: 10.1560/ijee.53.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Organ Size and Behavior of Red Knots (Calidris Canutus) Indicate the Quality of Their Benthic Food Stocks

Abstract: Digestive organ size anD behavior of reD knots (Calidris Canutus) inDicate the quality of their benthic fooD stocksAbSTRACT Assuming that animals respond optimally to environmental changes, both behavior and physiology should be useful indicators of the way that animals perceive the quality of their environment. For verification, we examined foraging time and gizzard size of the red knot (Calidris canutus), a long-distance migrant shorebird that ingests hard-shelled mollusk prey whole and therefore readily fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…This suggests that adaptive trade‐offs between these species involve different digestion strategies that influence growth efficiency, where steelhead may have a high food consumption strategy that strips out more labile energy with lower efficiency than coho, allowing them to achieve higher growth at high food abundance. Different digestive strategies to maximize energy assimilation are common among vertebrates (Milton 1981; Hume 1989; van Gils et al. 2007), but remain poorly documented among fish (see Nicieza, Reiriz & Brana (1994) and Millidine, Armstrong & Metcalfe (2009) for exceptions), but we suggest that they may underlie many of the adaptive trade‐offs related to growth that allow for differentiation and coexistence of ecologically similar species like salmonids.…”
Section: Discussionmentioning
confidence: 87%
“…This suggests that adaptive trade‐offs between these species involve different digestion strategies that influence growth efficiency, where steelhead may have a high food consumption strategy that strips out more labile energy with lower efficiency than coho, allowing them to achieve higher growth at high food abundance. Different digestive strategies to maximize energy assimilation are common among vertebrates (Milton 1981; Hume 1989; van Gils et al. 2007), but remain poorly documented among fish (see Nicieza, Reiriz & Brana (1994) and Millidine, Armstrong & Metcalfe (2009) for exceptions), but we suggest that they may underlie many of the adaptive trade‐offs related to growth that allow for differentiation and coexistence of ecologically similar species like salmonids.…”
Section: Discussionmentioning
confidence: 87%
“…Red knots eat hard-shelled molluscs that need to be crushed and processed internally, and gizzard size constrains the rate of food intake. Gizzard mass is a highly plastic trait (Dekinga et al 2001), but the growth and maintenance of a large gizzard takes time and energy (van Gils et al 2007). Indeed, gizzards of red knots measured in April 2007-2009 using ultrasonography (Dietz et al 1999) were somewhat smaller at A (8.8 g ± 2.9; n = 9) than at B (10.5 g ± 3.4; n = 77), but the differences were not significant (t-test: t = 1.6, df = 10.9, P = 0.14).…”
Section: Discussionmentioning
confidence: 99%
“…Arrival timing is a function of gizzard size, and could thus give an estimate of the quality of food that roost mates encountered (Fig. 3B, also between years it has been found that food quality determines daily foraging times, van Gils et al 2007). Given that individuals aim to maximise intake rate, thereby minimizing daily required foraging time, naïve or unsuccessful red knots could find the optimal prey type that matches their digestive capacity by following informed roost mates in similar state (i.e.…”
Section: Conceptual Model: Using Roost Arrival Timing As Information mentioning
confidence: 99%